2016
DOI: 10.1111/2047-3095.12149
|View full text |Cite
|
Sign up to set email alerts
|

The Nursing Diagnosis Development of Unemployment Disorder: Content Validation With Nursing Experts

Abstract: El índice de validez de contenido global fue 0.8690. Un total de 16 características definitorias alcanzaron carácter crítico (>0.80). CONCLUSIÓN: El presente estudio apoya la propuesta de elaborar un diagnóstico de enfermería para la respuesta humana al desempleo. IMPLICACIONES PRÁCTICAS: Los resultados obtenidos sugieren que la inclusión en la taxonomía NANDA-I del diagnóstico "trastorno por desempleo" permitiría a los profesionales de enfermería identificar el problema, sus causas y manifestaciones, y por lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
(103 reference statements)
0
5
0
1
Order By: Relevance
“…Para a seleção dos juízes deste estudo foi considerado o sistema de classi cação de experts a partir dos critérios adotados por Fehring e pesquisadores (18)(19)(20) , considerando experts apenas os participantes que alcançassem uma pontuação mínima de cinco pontos, seguindo a lógica de pontuação: Título de doutor = 4 pontos, Título de mestre = 3 pontos, publicação em periódico indexado sobre a temática de interesse do estudo = 2 pontos, Especialização na temática de interesse do estudo = 2 pontos, Prática clínica na área de interesse de no mínimo cinco anos na área de reabilitação = 2 pontos, Participação em evento cientí co nos últimos dois anos sobre a temática de interesse do estudo = 1 ponto. Tanto para a validação do roteiro quanto para validação do VE, foram convidados os mesmos 34 juízes selecionados pela amostragem intencional e bola de neve.…”
Section: Mßtodosunclassified
“…Para a seleção dos juízes deste estudo foi considerado o sistema de classi cação de experts a partir dos critérios adotados por Fehring e pesquisadores (18)(19)(20) , considerando experts apenas os participantes que alcançassem uma pontuação mínima de cinco pontos, seguindo a lógica de pontuação: Título de doutor = 4 pontos, Título de mestre = 3 pontos, publicação em periódico indexado sobre a temática de interesse do estudo = 2 pontos, Especialização na temática de interesse do estudo = 2 pontos, Prática clínica na área de interesse de no mínimo cinco anos na área de reabilitação = 2 pontos, Participação em evento cientí co nos últimos dois anos sobre a temática de interesse do estudo = 1 ponto. Tanto para a validação do roteiro quanto para validação do VE, foram convidados os mesmos 34 juízes selecionados pela amostragem intencional e bola de neve.…”
Section: Mßtodosunclassified
“…Items were generated through focus groups with diverse groups of unemployed people and healthcare experts, including people from university environments, nursing providers, and statistical experts as well as through the review of the scientific literature. USS items were specifically developed to reflect the current definition of unemployment syndrome developed by Bocchino et al (2017). A multidisciplinary panel comprised of content and methodological experts established the content validity of the USS.…”
Section: Ussmentioning
confidence: 99%
“…To this end, a recent proposal from a nursing diagnosis defines the conditions known as the unemployed syndrome as "a state of alteration in the physiological, psychological, and social reactions that people experience as a pathologic response to long-term unemployment" (Bocchino, Medialdea, Lepiani, Mejías, & Dueñas, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have shown how families with unemployed children and parents face a higher level of difficulty, with possible long-term consequences for the well-being and development of the child [ 10 , 11 , 12 , 13 ]. If the magnitude of these economic reduction effects is significant, it can lead to a series of devastating results for individuals and families who experience these effects to such a degree that they are able to speak of a new unemployment syndrome [ 14 ]. Recent research has shown how the unemployed syndrome has a series of negative repercussions on the health of people who suffer from it.…”
Section: Introductionmentioning
confidence: 99%